2009
DOI: 10.5539/ies.v2n4p140
|View full text |Cite
|
Sign up to set email alerts
|

Project Based Learning (PjBL) Practices at Politeknik Kota Bharu, Malaysia

Abstract: This study explores the utilization of Project-based Learning module in the subject of project development for the Mechanical Engineering students at Politeknik Kota Bharu.  This study focuses on the development of the PjBL module based on Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
4
0
4
Order By: Relevance
“…3) Abstraction: Identifying the general principles that generate these patterns or focusing only on the details and 4) Algorithm Design: that are important, whilst irrelevant information is ignored. Moreover, this tool should be used as a part of the computing science project-based learning that also enhances the cognitive and critical thinking in engineering problem solving among students (Rahman et al, 2009), which is expected to show more efficiency of this kind of learning management.…”
Section: Discussionmentioning
confidence: 99%
“…3) Abstraction: Identifying the general principles that generate these patterns or focusing only on the details and 4) Algorithm Design: that are important, whilst irrelevant information is ignored. Moreover, this tool should be used as a part of the computing science project-based learning that also enhances the cognitive and critical thinking in engineering problem solving among students (Rahman et al, 2009), which is expected to show more efficiency of this kind of learning management.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that the students' in the PoBL strategy perceived that they were more actively involved in exploration and that the process of PoBL helped them to understand the course concepts better. A study conducted by Rahman et al (2009) also indicated that the experimental group which was taught according to the PoBL strategy performed better in self-regulation in learning.…”
Section: Introductionmentioning
confidence: 94%
“…Di sini kaedah pembelajaran berpusatkan pelajar tidak berlaku dengan sepenuhnya dan pelajar lebih cenderung untuk menjadi pasif (Omar et al, 2012). Kaedah menyelia dan memantau yang sehala merupakan kaedah yang sering digunakan oleh setiap pengajar atau penyelia projek melalui kaedah pembelajaran konvensional (Rahman et al, 2009). Kaedah ini juga sukar untuk dijadikan penunjuk kepada hasil pembelajaran kerana tidak jelas dalam melihat seperti berkomunikasi dan kerja kumpulan di kalangan pelajar.…”
Section: Pembelajaran Berasaskan Projek (Pbpj)unclassified